2019
DOI: 10.1002/aet2.10376
|View full text |Cite
|
Sign up to set email alerts
|

The Revised METRIQ Score: A Quality Evaluation Tool for Online Educational Resources

Abstract: Background: With the rapid proliferation of online medical education resources, quality evaluation is increasingly critical. The Medical Education Translational Resources: Impact and Quality (METRIQ) study evaluated the METRIQ-8 quality assessment instrument for blogs and collected feedback to improve it.Methods: As part of the larger METRIQ study, participants rated the quality of five blog posts on clinical emergency medicine topics using the eight-item METRIQ-8 score. Next, participants used a 7-point Liker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…However, the ratings of small numbers of raters are insufficiently reliable. Further, our findings emphasize the need to develop tools that support podcast quality evaluation, which could build on the advances in quality evaluation of other open educational resources [ 12 14 , 24 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the ratings of small numbers of raters are insufficiently reliable. Further, our findings emphasize the need to develop tools that support podcast quality evaluation, which could build on the advances in quality evaluation of other open educational resources [ 12 14 , 24 ].…”
Section: Discussionmentioning
confidence: 95%
“…Studies have found the assessment of the quality of online resources to be difficult [7][8][9][10][11]. Resources have been developed to assist trainees and clinicians to assess the quality of blog posts [7,[12][13][14] but podcast listeners have had to rely upon their own gestalt to evaluate the quality of these resources. As the reliability of gestalt is limited by each individual's unique experience and learning needs [15,16], the effectiveness of this approach is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars in this space have proposed that we move beyond bibliometrics and surrogates for quality (eg, impact factor, citations, altmetrics), and that P&T committees consider applying direct quality assessments to items of interest (eg, applying the revised METRIQ 41 or ALiEM Approved Instructional Resources (AIR series) scores 39 to a few choice works of digital scholarship from a faculty member’s CV, or applying the PRISMA 42 reporting guidelines to a few systematic reviews). Equitably applying both descriptive bibliometrics (eg, citation rate, h-index, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In addition to relying on users' critical appraisal skills, there are suggested approaches and quality indicators (Lin et al 2015;Thoma et al 2018b;Colmers-Gray et al 2019). One systematic review identified three core themes for qualitycredibility (transparency, process, use of other resources, trustworthiness, and bias), content (professionalism, engagement, academic rigor, and orientation), and design (aesthetics, interaction, functionality, and ease of use) (Paterson et al 2015).…”
Section: Defining Quality In Social Mediamentioning
confidence: 99%